The Influence of Work Motivation, Work Environment, and Work-Life Balance on the Performance of Generation Z Employees in Lamongan Regency: Pengaruh Motivasi Kerja, Lingkungan Kerja, dan Work-Life Balance terhadap Kinerja Karyawan Generasi Z di Kabupaten Lamongan - Augusta I.M.H, Girawidana; Azar, Moh. Azus Shony; Rahmaniyah, Fatichatur (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Generation Z employees have become an increasingly important workforce group, requiring organizations to understand the factors associated with their performance. Specific Background: This quantitative explanatory study examined work motivation, work environment, and work-life balance in relation to Generation Z employee performance, using data from 150 purposively selected respondents and a 1–5 Likert-scale questionnaire. Knowledge Gap: Previous studies have discussed work-life balance, workplace conditions, and motivation among young employees, yet the integration of these three factors in one direct model remains limited within the studied context. Aims: This study aimed to test the partial and simultaneous relationships of work motivation, work environment, and work-life balance with Generation Z employee performance. Results: The findings show that work motivation had the strongest positive and significant coefficient (β = 0.457; p < 0.001), followed by work-life balance (β = 0.284; p = 0.003) and work environment (β = 0.278; p < 0.001). Simultaneously, the three variables were significantly associated with employee performance (F = 815.755; p < 0.001), with an Adjusted R Square of 0.943. Novelty: The study demonstrates that psychological and contextual factors jointly explain a very high proportion of Generation Z employee performance, with work motivation emerging as the dominant factor. Implications: Organizations should prioritize recognition, career development opportunities, supportive workplace conditions, and balanced work arrangements to strengthen sustainable Generation Z employee performance. Highlights• Work motivation shows the strongest coefficient among the tested variables.• Workplace conditions and balanced roles are significantly associated with performance.• The combined model explains 94.3% of employee performance variance. KeywordsWork Motivation; Work Environment; Work Life Balance; Employee Performance; Generation Z